Growth and survival assessment from African lungfish (Clarias gariepinus) and its hybrid with two species of heterobranchus - Abdulraheem, Ikililu; Abubakar, Musa Idi-Ogede (Universitas Malikussaleh, 2024)
Obtaining good quality and quantity of fish seeds for increasing fish production is a major quest by fish farmers. This study examined the growth responses and survival of Clarias gariepinus and two species of heterobranchus. One thousand five hundred (1500) fry (28-day after hatched) were randomly selected from each of the three crosses of Clarias gariepinus (T1), C. gariepinus x Heterobranchus longifilis (T2) and C. gariepinus x Heterobranchus bidorsalis (T3) broodstocks. They were stocked separately in triplicate at a stocking rate of 500 fish per replicate and reared for 90 days. The data were analysed for significant differences (P<0.05) by Analysis of Variance (ANOVA). There was no significant difference in the growth parameters but fish in T3 had the highest value of mean weight gain while T1 had the least. No significant difference (p>0.05) was observed in the body weight gains from day 40 to day 90 except at day 70 where T3 had the highest weight gain (18.97 g) which was significantly different (p<0.05) to the value recorded in T1 (18.20 g) but not significantly different (p>0.05) to the value recorded in T3 (18.97 g). The results of length increment showed that the growth pattern from day 0 to day 80 were similar. A little difference was observed at day 90 with T3 >T2>T1. The fish in T1 (Clarias gariepinus) had the highest significant percentage survival (89.60%). The results of water quality parameters showed that the mean temperature was 28oC, pH 6.8, dissolved oxygen 5.6 mg/l and turbidity 5.45 NYU. The culture of C. gariepinus by farmers will improve their output and consequentially increase in profit.Keywords: aquaculture; fish breeding; hybrids; weight gain